Regulatory issues and the potential use of Bayesian approaches for early drug approval systems in Japan. (7th January 2022) - Hirakawa, Akihiro; Sato, Hiroyuki; Igeta, Masataka; Fujikawa, Kei; Daimon, Takashi; Teramukai, Satoshi
Abstract: Bayesian methods quantify and interpret the therapeutic effects of investigational drugs based on probability statements of the posterior distribution. However, the basic principle underlying the use of Bayesian methods in registration trials for new drug applications in Japan has not been adequately discussed. Motivated by the two drug approval systems for early approval recently enacted in Japan, we present our perspectives on the application of the Bayesian approach in registration trials in Japan. These are based on discussions among academic, industry, and regulatory experts at invited workshops. Based on the aforementioned early approval systems, we discuss putative common regulatory issues related to the use of the Bayesian approach and introduce instances of clinical trials in which the Bayesian approach is expected to be used. This article provides a well‐defined premise for the discussion between industry and regulatory agencies on the use of Bayesian approaches for early drug approval in Japan.